2019
DOI: 10.1249/mss.0000000000001752
|View full text |Cite|
|
Sign up to set email alerts
|

Equivalent Hypertrophy and Strength Gains in β-Hydroxy-β-Methylbutyrate- or Leucine-supplemented Men

Abstract: HMB added to whey did not result in greater increases in any measure of muscle mass, strength, or hormonal concentration compared to leucine added to whey. Our results show that HMB is no more effective in stimulating RT-induced hypertrophy and strength gains than leucine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 40 publications
7
27
0
Order By: Relevance
“…Kraemer et al [4], Wilson et al [8], and Lowery et al [6] observed gains of about 7 to 8 kg FFM in subjects supplemented with 3 g of HMB per day. Our results are more in line with data recently published by Jakubowski et al [20], who reported 2.3 kg and 2.6 kg gains in whole-body FFM after 12-weeks of resistance training with protein plus HMB (3 g per day) and protein plus leucine (3 g per day) supplementation, respectively. Such moderate increases in FFM are also supported by a recent meta-analysis, showing that with total protein intake of at least 1.6 g•kg − 1 •day − 1 training-induced gains in FFM can reach a maximum of about 4 kg with an average of about 1.5 kg [38].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Kraemer et al [4], Wilson et al [8], and Lowery et al [6] observed gains of about 7 to 8 kg FFM in subjects supplemented with 3 g of HMB per day. Our results are more in line with data recently published by Jakubowski et al [20], who reported 2.3 kg and 2.6 kg gains in whole-body FFM after 12-weeks of resistance training with protein plus HMB (3 g per day) and protein plus leucine (3 g per day) supplementation, respectively. Such moderate increases in FFM are also supported by a recent meta-analysis, showing that with total protein intake of at least 1.6 g•kg − 1 •day − 1 training-induced gains in FFM can reach a maximum of about 4 kg with an average of about 1.5 kg [38].…”
Section: Discussionsupporting
confidence: 93%
“…The changes in 1-RM were in a typical range reported in previous 12-week resistance training studies for bench press [3,8,20] and leg press [3], but considerably lower than those reported by Kraemer et al [4] and Lowery et al [6]. Some of these studies reported no [20] or a slight effect [3] of HMB on 1-RM gains, whereas others found a strong effect [4,6,8]. Our findings were in line with a study by Gallagher et al [42] that examined the effects of HMB, administered in doses of 0 g, 3 g or 6 g per day on FFM and strength during eight weeks of resistance training in 37 untrained men [42].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations